ANALYSIS OF THE INFLUENCE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN PERSPECTIVE ISLAM ON JOB SATISFACTION - Raihanah Daulay; Irma Christianaf; Susi Handayani (Proceeding International Seminar of Islamic Studies, 2022)
: Job satisfaction is a condition in which an individual feels good about what he has done from a job. A sense of satisfaction will give you better work. Employee job satisfaction has a good effect on the creation of company performance. Many factors that can provide employee job satisfaction include organizational citizenship behavior. This study aims to find out and analyze the influence of organizational citizenship behavior in Islamic perspectives on job satisfaction. This study is an associative study with a research sample of 80 respondents who are employees at higher education institutions in Medan. Data clumping techniques use observation and coesioner. Data analysis techniques use regression analysis, as well as hypothesis tests. The results showed that organizational citizenship behavior variables affect job satisfaction and the contribution of indevenden variables to job satisfaction 24.2%.Keywords: Islamic perspective, Job satisfaction, Organizational Citizenship Behavior, Performance